Codification of the law of the sea - Anechitoae, Constantin (Technium Social Sciences Journal, 2023)
By codifying the law of the sea, its rules are systematized. From the point of view of how the codification of the law of the sea is carried out, it can be: unofficial codification and official codification. The unofficial codification of the law of the sea is carried out in the form of numerous codification projects developed by some doctrinaires. Unofficial coding is not mandatory for its subjects. The official codification of the law of the sea is carried out by the states. It has a binding character for the subjects of the law of the sea, insofar as they recognize the codification acts (becoming parties to the codification conventions).